FACTORS OF ENVIRONMENTAL CRIME: A CRIMINOLOGICAL APPROACH - Alfredo Rynaldi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This research examines environmental crimes based on case studies in Indonesia through the perspective of environmental criminology theory. Using the literature study method, this research explores the driving factors of environmental crimes. The results show that weak environmental law enforcement, corruption, administrative failure, social and economic inequality, and criminal conspiracy by corporations and the state are significant factors that contribute to environmental crimes. Thus, theoretically, environmental criminology theory is able to provide the causes of environmental crimes as well as the perpetrators and victims of environmental crimes.